2018
DOI: 10.1097/acm.0000000000002375
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Knowledge Resources and Point-of-Care Learning: A Scoping Review

Abstract: Purpose The authors sought to summarize quantitative and qualitative research addressing electronic knowledge resources and point-of-care learning in a scoping review. Method The authors searched MEDLINE, Embase, PsycINFO, and the Cochrane Database for studies addressing electronic knowledge resources and point-of-care learning. They iteratively revised inclusion criteria and operational definitions of study features and research themes of interest. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…They have been trained, and often attempt, to answer these questions using a variety of resources, including increasing use of electronic resources [2-4]. Electronic knowledge resources have been defined as “electronic (computer-based) resources comprising distilled (synthesized) or curated information that allows clinicians to select content germane to a specific patient to facilitate medical decision making” [5]. Commonly used electronic knowledge resources include commercial products, such as UpToDate, Micromedex, and Epocrates [6,7]; locally developed products, such as McMaster Premium LiteratUre Service (PLUS) [8]; and crowdsourced resources, such as Wikipedia [9].…”
Section: Introductionmentioning
confidence: 99%
“…They have been trained, and often attempt, to answer these questions using a variety of resources, including increasing use of electronic resources [2-4]. Electronic knowledge resources have been defined as “electronic (computer-based) resources comprising distilled (synthesized) or curated information that allows clinicians to select content germane to a specific patient to facilitate medical decision making” [5]. Commonly used electronic knowledge resources include commercial products, such as UpToDate, Micromedex, and Epocrates [6,7]; locally developed products, such as McMaster Premium LiteratUre Service (PLUS) [8]; and crowdsourced resources, such as Wikipedia [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has focused on interventions to either increase the use of, or nd new ways of using, electronic knowledge sources, whereas this study speci cally examined the effect of the use of a knowledge base on patient outcome measures in two nationwide registries. Earlier studies have found that use of register data may play a vital role in patient care (12,15,36). Furthermore, an excess of research has been devoted to evaluating electronic knowledge sources by employing self-reported use, which is prone to biases (37-39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has focused on interventions to either increase the use of, or find new ways of using, electronic knowledge sources, whereas this study specifically examined the effect of the use of a KB on patient outcome measures in two nationwide registries. Earlier studies have found that use of register data may play an vital role in patient care (12,15,32). Furthermore, an excess of research has been devoted to evaluating electronic knowledge sources by employing self-reported use, which is prone to biases (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used Lobach's definition of a KB: "Electronic (computer-based) resources comprising distilled (synthesized) or curated information that allows clinicians to select content germane to a specific patient to facilitate medical decision making" (14). The use of KBs is associated with a positive impact on clinician behavior and patient outcomes, and evidence suggests that use of KBs may be associated with improved knowledge and patient outcomes (12,15,16).…”
Section: Introductionmentioning
confidence: 99%